Holistic evolution of the Bohai Sea complex system: Insights from interacting drivers - Han Huang; Tao Zou; Teng Liu; Hongyu Wang; Zhixuan Wang; Ningning Tao; Yanfang Li; Hao Fan; Fei Xie; Weidong Zhai; Guizhi Wang; Yongwen Zhang; et al. (Marine Environmental Research, 2026)

Complex network approaches for identifying global drought teleconnection patterns - Wenliang Wang; Lei Zhou; Congcong He; Yongwen Zhang; Zhiqiang Gong; Na Ying; Panjie Qiao; Jianjun Wu; Hongquan Sun; Jingfang Fan (Global and Planetary Change, 2025)

MoO3-MoS2 with abundant oxygen vacancies for real-time seafood quality assessment - Guochen Qi; Shuwei Ren; Jingfang Ji; Hao Gao; Zhichuang Ma; Sufeng Fan; Pan Liu; Jingmin Ge (Chemical Engineering Journal, 2025)

Fuels Mediate the Influence of Climate Teleconnections on Wildfires in Dryland Ecosystems - Yuquan Qu; Sander Veraverbeke; Diego G. Miralles; Jingfang Fan; Harry Vereecken; Carsten Montzka (Global Change Biology, 2025)
Climate teleconnections modulate regional wildfire occurrence. Understanding the underlying mechanisms is critical for sub‐seasonal to annual wildfire predictions since the magnitude of certain teleconnection climate modes (TCMs) intensifies or they may undergo phase shifts. Here, we study how TCMs govern wildfire activity and compare the effects of weather and fuels in mediating the influence of TCMs on wildfires. Globally, burned area (BA) is predictable by a single TCM in 25.4% of the burnable (vegetated) regions, with Australia and eastern Siberia identified as the two hot spots with the highest probability out of a total of 10. Tropical oceans are the primary sources of teleconnection‐driven variability in global BA. Our study finds that in dryland hot spots such as Australia, the Horn of Africa, and the northern Middle East, the lagged mediating effects of fuels outweigh the immediate mediating effects of weather. Whereas in hot spots with dense vegetation, like northeastern South America and Southeast Asia, the immediate mediating effects of weather are generally more dominant. In other hot spots, fuels can still serve as a key pathway through which specific TCMs influence wildfire activity. This study highlights the important role of fuels in transmitting the delayed impacts of TCMs‐induced weather anomalies on regional wildfire activity. This study also underlines the importance of refining fuel management strategies and integrating fuel conditions in teleconnection‐related wildfire attribution and prediction frameworks, which is crucial given the projected changing patterns of teleconnections.

Comprehensive study of heavy precipitation events over land using climate network analysis - Kaiwen Li; Ming Wang; Kai Liu; Jingfang Fan (Journal of Hydrology, 2025)

Synchronization patterns of extreme rainfall events in Southwest China - Panjie Qiao; Xiaojuan Wang; Wenqi Liu; Shuai Li; Yongwen Zhang; Guolin Feng; Jingfang Fan (Climatic Change, 2025)

Complexity science meets Earth system - Jingfang Fan; Jun Meng; Xiaosong Chen; Hans Joachim Schellnhuber (Science Bulletin, 2025)

Quaternary pollen record and paleoenvironmental evolution of the Bohai Sea strait - Jingfang Lu; Wei Huang; Jun Sun; Feifei Wang; Yuexin Gao; Xin Fan; Daolai Zhang (Regional Studies in Marine Science, 2023)

Complete genome sequence of a novel lytic bacteriophage isolated from Ralstonia solanacearum - Jingfang Su; Hongwei Sun; Junjie Liu; Zhaokui Guo; Guoquan Fan; Gang Gu; Guanghua Wang (Archives of Virology, 2017)